Impact of Employee Stock Options on the Market Capitalization of the Company - Jain, Natika Pravin (Indian Journal of Finance, 2010)
Employee stock option plans (ESOP’s) are becoming popular in India especially for executives in Information Technology firms. In this case, specific types of employees are allotted the company’s shares below the market price. This allotment can be made to employees as an alternative to the bonus payable to them. In case of better financial results, the market price of the company’s shares as well as the value of the employee’s shareholding increases. It can be used as a profit sharing arrangement by which employees receive, in addition to wages, the company’s shares.An employee stock option is a contract that gives the employees the right, but not an obligation, to subscribe to an entity’s shares at a fixed or determined price for a specified period of time. ESO grants help companies to attract and motivate key employees and they align shareholder interests (i.e., an increase in share prices) with the interests of grantees (i.e., an increase in option value). Academic studies demonstrate that granting options can contribute to improving corporate performance by enabling companies to attract and retain talented people who are critical to the company’s success. This is particularly true in sectors where the market opportunities are very large and technology changes are very rapid. In addition, options enable young companies to reduce their cash usage and thus avoid issuing stock at unfavorable current valuations. People think that both ESO and Call Options are same because of the similarity of the fundamental function. But they differ and the important distinction is that ESOPs, unlike call options, are corporate securities that are issued by the corporations. Employees Stock Options (ESOPs) have been one of the most controversial topics in financial reporting during the last decade.